A gendered study of the working patterns of classical musicians: implications for practice - Bennett, Dawn (SAGE publishers, 2008)
Despite an increase in participation at all levels of the music profession, women continue to experience less opportunities to forge careers in music and are less likely than men to apply for leadership positions. This paper presents results from a study in which 152 instrumental musicians reflected upon their professional practice and career aspirations. The study examined differences in the professional practice of male and female musicians, and found female musicians to be more likely to teach, and less likely to sustain performance positions due to the difficulties associated with managing family and other commitments whilst maintaining an uninterrupted career in music. It is proposed that educators have a crucial role to play in the development of curricula reflective of the realities of professional practice in a profession where interrupted careers can result in a loss of technical skills and outdated curricular and methodological knowledge.